Inverse backscattering problem for perturbations of biharmonic operator. (7th September 2017) - Tyni, Teemu; Harju, Markus
Abstract: We consider the inverse backscattering problem for a biharmonic operator with two lower order perturbations in two and three dimensions. The inverse Born approximation is used to recover jumps and singularities of an unknown combination of potentials. Numerical examples are given to illustrate the practical usefulness of the method.